HIV-1 transcripts use IRES-initiation under conditions where Cap-dependent translation is restricted by poliovirus 2A protease. - Raquel Amorim; Sara Mesquita Costa; Nathalia Pereira Cavaleiro; Edson Elias da Silva; Luciana Jesus da Costa (PLoS ONE)
The 30 different species of mRNAs synthesized during the HIV-1 replication cycle are all capped and polyadenilated. Internal ribosome entry sites have been recognized in the 5' untranslated region of some mRNA species of HIV-1, which would contribute to an alternative mechanism of initiation of mRNA translation. However, the Cap-dependent translation is assumed to be the main mechanism driving the initiation of HIV-1 protein synthesis. In this work, we describe a cell system in which lower to higher levels of transient expression of the poliovirus 2A protease strongly inhibited cellular Cap-dependent translation with no toxic effect to the cells during a 72-hour time frame. In this system, the synthesis of HIV-1 proteins was inhibited in a temporal dose-dependent way. Higher levels of 2A protease expression severely inhibited HIV-1 protein synthesis during the first 24 hours of infection consequently inhibiting viral production and infectivity. Intermediate to lower levels of 2A Protease expression caused the inhibition of viral protein synthesis only during the first 48 hours of viral replication. After this period both protein synthesis and viral release were recovered to the control levels. However, the infectivity of viral progeny was still partially inhibited. These results indicate that two mechanisms of mRNA translation initiation contribute to the synthesis of HIV-1 proteins; during the first 24-48 hours of viral replication HIV-1 protein synthesis is strongly dependent on Cap-initiation, while at later time points IRES-driven translation initiation is sufficient to produce high amounts of viral particles.